Angiotensin AT1-Receptor Blockers Enhance Cardiac Responses to Parasympathetic Nerve Stimulation via Presynaptic AT1 Receptors in Pithed Rats - Fumiko Yamaki; Takanori Arai; Masato Aoyama; Akane Watanabe; Yoshinobu Takata (Elsevier, 2013)
Abstract.: In the present study, we investigated the effects of angiotensin AT1-receptor blockers, KT3-671 and losartan, on the cardiac vagal neurotransmission in pithed rats. The bradycardia induced by vagal nerve stimulation (VNS, at 5 Hz) was potentiated significantly and dose-dependently by KT3-671 and also losartan. This enhancement effect of KT3-671 (10 mg/kg) was slightly potent than that of losartan (10 mg/kg). On the other hand, an angiotensin AT2-receptor blocker, PD123319 (10 mg/kg), did not affect VNS-induced bradycardia. KT3-671 and losartan did not affect the exogenous acetylcholine-evoked bradycardia. Intravenous infusion of AngII (100 ng/kg per min) attenuated the VNS-induced bradycardia. This inhibitory effect of AngII on bradycardia was restored by both KT3-671 and losartan. These results suggest that endogenous AngII can have a tonic inhibitory effect on cardiac vagal transmission by stimulating the presynaptic AT1 receptors not AT2 receptors. Suppression of this mechanism by the AT1-receptor blockers causes the facilitation of acetylcholine release from vagal nerve endings. This acceleratory effect of AT1-receptor blockers on cardiac vagal neurotransmission may contribute to the lack of reflex tachycardia following hypotension. Keywords:: angiotensin AT1-receptor blocker, angiotensin II, vagal neurotransmission, bradycardia, rat heart